P710 Evaluation of helminth extracellular vesicles as a novel therapeutic for inflammatory bowel disease in murine models of colitis. (21st January 2022) - Bray, G; Giacomin, P
Abstract: Background: With the increasing complexity of inflammatory bowel disease (IBD) new therapies are clearly required. Recent evidence is coming to light demonstrating beneficial effects of helminth proteins. We aim to assess the prophylactic and therapeutic effects of extracellular vesicles (EVs) from the nematode N. brasiliensis, which serves as a model organism for human hookworm infections, in an acute and chronic model of colitis. Methods: Prophylactic and therapeutic effects of EVs were assessed in an acute model of colitis by the administration of 20µg intraperitoneally (i.p) of Nb EVs or grape EVs. Mice were sacrificed after 5 days. The therapeutic effects of Nb EVs were also assessed in a chronic model of colitis. Here, Rag1 knockout mice were treated twice weekly for three weeks with 20µg of either Nb EV, grape EV or aIL-12. Outcomes assessed for both experiments included weight loss, clinical disease, as well as macroscopic and histologic disease scores. Groups were statistically compared for significant differences. Results: The prophylactic administration of Nb EVs significantly reduced weight loss, clinical disease, and histologic pathology compared to grape EV-treated negative controls. Therapeutic administration of Nb EVs significantly reduced weight loss and histologic pathology in the colon. Conclusion: The current study provides important evidence that the anti-inflammatory effects of helminth EVs can be harnessed to prevent and reverse inflammation in an acute and chronic mouse model of colitis. With further characterization of helminth EVs, these compounds have the potential to generate much needed new anti-inflammatory therapies for IBD.